Reviewing Legal Justice, Certainty, and Legal Expediency in Government Regulation Number 24 of 2018 Concerning Electronically Integrated Business Services - Wicaksono, Raden Mas Try Ananto Djoko (Universitas Negeri Semarang, 2021)
This study conducted a legal review of Government Regulation Number 24 of 2018 as the forerunner to the formation of OSS. Aims to analyze the elements of justice, legal certainty and legal expediency in accordance with the objectives of the formation of law. This research is a normative juridical research with the technique of collecting material from the literature consisting of primary and secondary legal materials. The results show that the application and enactment of OSS on the basis of Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services is not in accordance with legal objectives. This is due to the absence of a transition period in the enactment of the regulations and provides an opportunity for the community and / or business actors to learn and adapt to a system that is completely new in the world of business licensing.